2020
DOI: 10.1080/2162402x.2020.1824645
|View full text |Cite
|
Sign up to set email alerts
|

Association of baseline systemic corticosteroid use with overall survival and time to next treatment in patients receiving immune checkpoint inhibitor therapy in real-world US oncology practice for advanced non-small cell lung cancer, melanoma, or urothelial carcinoma

Abstract: Immune checkpoint inhibitors (CPIs) have expanded treatment options for patients with solid tumors. Systemic corticosteroids (CSs) have an indispensable role in cancer care, but CS-related immunosuppression may counteract the CPI-driven antitumor immune response. This retrospective study investigated the association between baseline CS use (bCS; ≤14 days before, ≤30 days after CPI initiation) and clinical outcomes in patients with advanced non-small cell lung cancer (aNSCLC), melanoma (aMel), or urothelial car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Additionally, patients with AID often require immunosuppressive treatment, which may compromise ICI efficacy. 4 Regarding the efficacy and overall toxicity of ICI in the AID population, in the first retrospective study of anti-PD-1 in AIDs, the objective response rate (ORR) was 33% in patients with melanoma, AID flares were common at 38% (6% grade 3) but otherwise 'conventional' irAEs occurred at rates similar to those previously reported in clinical studies (29% overall, 10% grade 3). 5 Subsequent retrospective studies of agents blocking PD-1 or its ligand (PD-L1) [primarily in melanoma and non-small-cell lung cancer (NSCLC)] reported similar findings (ORR: 22%-54%; AID flares: 6%-42%; irAEs: 16%-38%).…”
Section: Autoimmune Conditionssupporting
confidence: 58%
“…Additionally, patients with AID often require immunosuppressive treatment, which may compromise ICI efficacy. 4 Regarding the efficacy and overall toxicity of ICI in the AID population, in the first retrospective study of anti-PD-1 in AIDs, the objective response rate (ORR) was 33% in patients with melanoma, AID flares were common at 38% (6% grade 3) but otherwise 'conventional' irAEs occurred at rates similar to those previously reported in clinical studies (29% overall, 10% grade 3). 5 Subsequent retrospective studies of agents blocking PD-1 or its ligand (PD-L1) [primarily in melanoma and non-small-cell lung cancer (NSCLC)] reported similar findings (ORR: 22%-54%; AID flares: 6%-42%; irAEs: 16%-38%).…”
Section: Autoimmune Conditionssupporting
confidence: 58%
“…Importantly, this association was confirmed in a multivariate analysis, and to our knowledge this is the first study to indicate that the development of irAEs treated with steroids represents an independent predictor of ICIs’ efficacy. Intriguingly, a potential association with better prognosis in patients reporting irAEs has been previously described [ 34 , 35 , 36 ], thus balancing the immunosuppressive effect of steroid use. This is an important message to clinical oncologists, underlying the relevance of a rapid and appropriate steroid treatment in patients who experience irAEs precisely due to their better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 11 studies reported the OSs following corticosteroid administration of patients with NSCLC under ICI therapy 11‐13,18‐20,22–26 . The pooled HR was 1.82 (95% CI, 1.51–2.18), indicating that the patients receiving corticosteroid therapy have significantly worse survivals than those not receiving corticosteroid therapy (Figure 2).…”
Section: Resultsmentioning
confidence: 99%